Synchronization of City Branding and Tourist Visit Interest using the Triple Helix Concept: The Case of Banyuwangi Rebound during the COVID-19 Pandemic - Ahmadintya Anggit Hanggraito; Indira Nuansa Ratri; Esa Riandy Cardias (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
The purpose of this study was to examine the relationship between the variable City branding and Tourist Visit Interest who have synchronized with the triple helix concept that runs in tourism in Banyuwangi district. City branding can be one way to increase Tourist Interest. The triple helix concept that was built connects these two variables because there are many stakeholders whose roles were affected during the COVID-19 pandemic. The Banyuwangi District Government is running a city branding program as an effort to restore the various pillars built in to Triple Helix Model. The method used is a mixed-methods type embedded design. For quantitative data analysis using SEM-PLS with a sample of 37 people. Then, to interpret the results, a qualitative descriptive analysis is needed through the results of focus group discussions and in-depth interviews with business actors and academics as part of the triple helix. The study indicates that the relationship between branding image and tourist interest has a latent variability of 42.0% in the structural model test results. This variable relationship in the Banyuwangi Rebound program has with the triple helix concept, especially in the business sector and academics in practice during the COVID-19 pandemic.